The relationship between broad money and stock prices in Malaysia: an Error Correction model approach - Habibullah, Muzafar Shah (Penerbit Universiti Kebangsaan Malaysia, 1998)
The purpose of this study is to investigate the empirical relationship between money supply and stock prices in the Kuala Lumpur Stock Exchange (KLSE), using monthly data that span from January 1984 to September 1992. Specifically, we test for market informational efficiency in KLSE by testing the causal relationships between money supply, M3 and stock prices using the cointegration technique. Results from our Error Correction models suggest that the informational efficiency markets hypothesis can be rejected for the KLSE.